Pengawasan PERDA Kabupaten Labuhan Batu No.2 Tahun 2020 tentang Pertanggung Jawaban Pelaksanaan APBD - Abdul Karim Hasibuan (Jurnal Smart Hukum (JSH), 2022)
Supervision of the implementation of regional regulations has an important meaning. The party that plays a role in supervision at the regional level is the DPRD. The formulation of the problem in this research is how is the supervisory system for the Labuhan Batu Regency Regulation No. 2 of 2020, how is the supervisory authority of the Labuhan Batu Regency Regulation No. 2 of 2020 concerning Accountability for the Implementation of the Regional Revenue and Expenditure Budget, how are the obstacles to implementing APBD supervision by the Regional People's Representative Council Labuhan Batu Regency and efforts to overcome it. This study uses a descriptive method through a normative approach (legal research) to obtain secondary data. The collected data will be analyzed carefully using qualitative analysis or described in sentences. The supervision of the Labuhan Batu Regency Regional Regulation No. 2 of 2020 concerning Accountability for the Implementation of the Regional Budget carried out by the Labuhan Batu DPRD has been running optimally. The strict supervision process carried out by the DPRD will have a positive impact on the APBD in Labuhan Batu Regency. The supervisory authority of the Labuhan Batu Regency Regional Regulation No. 2 of 2020 concerning Accountability for the Implementation of the Regional Budget is through unscheduled monitoring in accordance with developing needs. The results of the study show that the obstacles to implementing APBD supervision by the Labuhan Batu Regency DPRD are internal obstacles, namely the lack of expertise of DPRD members in certain fields that are the object of supervision, DPRD Human Resources who lack the ability, communication that is not in line with other factions.